Polymer-Surfactant Formulation Design Optimization For CO2 Mobility Control For Enhanced Oil Recovery Applications - Clarence , Yong Yee Hern (IRC, 2016)
Enhanced oil recovery (abbreviated EOR) is the implementation of various techniques for increasing the amount of crude oil that can be extracted from an oil field. Enhanced oil recovery is also called improved oil recovery or tertiary recovery (as opposed to primary and secondary recovery). Thus, the correct chemical interaction between the subsequent flow conformance of the EOR sweep efficiency to recover more oil and rapidly. The expectation for this experiment is to have higher sweep efficiency to extract more oil by using the correct selection of samples. In order to make this possible, we have to conduct experiments to prove our results. Firstly we have to screen the best surfactant and best polymer solution by mixing surfactants, polymers and foam booster.